Penyusunan Standard Operating Procedure untuk Incident Management dan Problem Management Aset Digital Pada Perusahaan XYZ Berdasarkan Pedoman Information Technology Infrastructure Library - Nadya Rahmasari; Admaja Dwi Herlambang; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
XYZ Company is a company engaged in the services of national water resources. XYZ Company has RITI or IT Master Plan who has covered overall IT management, including management of Digital Archives commonly called Digital Assets. In this study, ITIL has been chosen as a guideline to be used. Researchers focus on Incident Management and Problem Management Domain. Interviews and observation will be used as a method to data search. Interviewees were obtained from the mapping of the RACI Chart. The obtained data will be analyzed using an analysis of the current and ideal conditions then followed by a gap analysis. The results of the gap analysis will be a solution to the company. The solution is the output from this research in the form of a draft Standard Operating Procedure which will be prepared based on the activities contained in the ITIL Guidelines Incident Management and Problem Management Domain. The making of the SOP will be carried out based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia No. 35 of 2012 concerning Guidelines for the Preparation of Operational Standards for Government Administration Procedures. This research produces SOP in each domain. Domain Incident Management produced 3 series of SOPs, 16 activities and 2 supporting forms. Meanwhile, the Problem Management domain produced 4 series of SOPs, 19 activities, and 3 supporting forms.